1978
DOI: 10.1021/bi00619a036
|View full text |Cite
|
Sign up to set email alerts
|

An infrared spectroscopic study of carbon monoxide bonding to ferrous cytochrome P-450

Abstract: Ferrous-carbonyl complexes of the soluble Pseudomonas putida cytochrome P-450,,, and a denatured form (P-420) of this enzyme, as well as cytochromes P-450 and P-448 in liver microsomes from rats pretreated with phenobarbital and 3-methylcholanthrene, have been studied by infrared spectroscopy. The FeCO bonding was examined in order to probe the spatial relationship between the dioxygen-and substrate-binding sites and to determine whether the presence of a unique axial ligand bound trans to carbon monoxide coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
37
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 58 publications
(84 reference statements)
16
37
0
Order By: Relevance
“…The 1969 cm ±1 band is assigned to a solvent-exposed FeCO unit (form III), where the CO ligand undergoes random interactions with the negative end of the water dipoles which is reported to broaden and blue-shift the n(CO) band [45]. In support of this assignment, a similar n(CO) band was reported for thermally denatured HRPC-CO (1964 cm ±1 ) [40], acid-denatured myoglobin-CO (1966 cm ±1 ) [46] and base-denatured cytochrome P 450 -CO (1966 cm ±1 ) [47]. A second marker of acid-denatured HRPC-CO is the reversal of the positive and negative CD bands, as seen in Fig.…”
Section: Discussionsupporting
confidence: 64%
“…The 1969 cm ±1 band is assigned to a solvent-exposed FeCO unit (form III), where the CO ligand undergoes random interactions with the negative end of the water dipoles which is reported to broaden and blue-shift the n(CO) band [45]. In support of this assignment, a similar n(CO) band was reported for thermally denatured HRPC-CO (1964 cm ±1 ) [40], acid-denatured myoglobin-CO (1966 cm ±1 ) [46] and base-denatured cytochrome P 450 -CO (1966 cm ±1 ) [47]. A second marker of acid-denatured HRPC-CO is the reversal of the positive and negative CD bands, as seen in Fig.…”
Section: Discussionsupporting
confidence: 64%
“…In **. _t*~*, ..... this context it was shown that NO binds to CYP heme groups with high affinity (10) and that other hemoproteins, such as the cyclooxygenase or the lipoxygenase, are also inhibited by NO (35,36). However, in a former study we have demonstrated by electron paramagnetic resonance (EPR) that predominantly nonheme iron-nitrosyl complexes are formed by NO in hepatocytes (37).…”
Section: Resultsmentioning
confidence: 99%
“…Many of these effects are based on modulation of enzyme activity through binding of NO to prosthetic iron complexes. In this context it is interesting that NO was used for years as a spin-label probe to investigate the role of heme groups in the catalytic centers of cytochrome P450 (CYP) enzymes (10). Consequently, it was demonstrated that NO inhibits CYPdependent reactions when microsomal preparations were exposed to NO (11).…”
Section: S-nitrosylacetylpenicillamine Led To a Concentration-dependentmentioning
confidence: 99%
“…The P4503P420 conversion was first described by Omura and Sato (31), by using snake venom-or deoxycholate-treated rabbit liver microsomal P450 preparations. Subsequently, it has been shown that P4503P420 transitions may be induced by temperature or pressure perturbations (9,16), as well as treatment with various chemicals (17) or pH extrema (28). Some of these treatments have been exploited to investigate P450 structural architecture and prosthetic group ligand coordination (24).…”
Section: Discussionmentioning
confidence: 99%